Interactions of phenolic compounds with ovalbumin: a spectroscopic approach - Vapor, Alcides (2019)
Ovalbumin (OVA) is the major protein in egg white and can cause allergy mainly in infants and young children. Egg allergy is an IgE mediated reaction and is one the most common food allergies. So far, the avoidance of the egg has been the unique way to prevent this allergy. It is well known that phenolic compounds can bind to proteins promoting structural and functional changes and, phenolic compounds are been recognized as having a potent antioxidant, anti-inflammatory and antitumoral activity. In this work, the interactions between OVA and the phenolic compounds were studied through spectroscopic techniques (fluorescence, circular dichroism (CD), Fourier transform infrared spectroscopy (FTIR)) and docking. spectroscopy (FTIR)) and docking.